The study of polycyclic aromatic hydrocarbons in particulate fractions emitted by office printers and copiers - Małgorzata Szewczyńska; Małgorzata Pośniak; Joanna Kowalska (Nofer Institute of Occupational Medicine, 2014)
Background: This article presents the study of polycyclic aromatic hydrocarbons (PAHs) adsorbed on fine particles emitted during the simulated operation of office printers and copiers. Material and Methods: In the study three types of printers, and four types of office copiers were used. Measurements were carried out in a closed measuring chamber. Air samples (fractions of particulate matter, PM10 and PM2.5) were collected on Teflon filters. The analysis of PAHs was carried out according HPLC/FL. Results: The results of qualitative analysis of filters from PM2.5 and PM10 type samplers indicated the presence of the majority (10-14) of PAH congeners. The highest concentration of total PAHs was determined in the PM10 fraction in the air during the operation of a copier, and amounted to 36.52 μg×g-1. The total content of PAHs as determined in the fraction of fine particulates, size of < 2.5 μm, accounts for 48-84% of the PAH content in the < 10 μm fraction for printers and 63-89% for copiers. During the operation of both printers and copiers, benzo(a)pirene (BaP) was identified in both fractions, PM2.5 and PM10. The maximum concentration of BaP in the fraction of < 10 μm particles emitted by a printer amounted to 3.29±0.2 μg×g-1. Conclusions: The studies showed that the composition of emitted substances and fine particles depends on the type of equipment and technology used. Fine particles emitted to the environment and organic compounds, including PAHs adsorbed on them may pose a threat to people working in such an environment. Med Pr 2014;65(6):733-741